2007
DOI: 10.1007/s00531-007-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the landscape change at River Basin scale based on SPOT and TM fusion remote sensing images: a case study of the Weigou River Basin on the Chinese Loess Plateau

Abstract: Eco-environmental changes which generally manifest as the ecological landscape changes are mainly affected by natural and human factors. Through complex interaction, natural factors and human activities alter the landscape structure and decide the service function of regional ecosystem. With the development of geographical information system (GIS) and satellite remote sensing (RS) techniques, the researches on quantitative analysis of landscape changes have made great strides forward. In this paper, the landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A collection of classes makes up the landscape. Several studies have explored fragmentation at these scales [22,39,[44][45][46]. Exploring the relationship between LULCC, the drivers of change, and the ecological implications of such changes, Kabba and Li [45] concluded that fragmentation at the class and landscape scales in Wuhan, China was greatest in 1987-1994 but weakened in 1994-2005, leading first to species loss in the fragmented areas followed by a return of species as fragmented habitat areas re-aggregated.…”
Section: Landscape Fragmentationmentioning
confidence: 99%
See 3 more Smart Citations
“…A collection of classes makes up the landscape. Several studies have explored fragmentation at these scales [22,39,[44][45][46]. Exploring the relationship between LULCC, the drivers of change, and the ecological implications of such changes, Kabba and Li [45] concluded that fragmentation at the class and landscape scales in Wuhan, China was greatest in 1987-1994 but weakened in 1994-2005, leading first to species loss in the fragmented areas followed by a return of species as fragmented habitat areas re-aggregated.…”
Section: Landscape Fragmentationmentioning
confidence: 99%
“…Exploring the relationship between LULCC, the drivers of change, and the ecological implications of such changes, Kabba and Li [45] concluded that fragmentation at the class and landscape scales in Wuhan, China was greatest in 1987-1994 but weakened in 1994-2005, leading first to species loss in the fragmented areas followed by a return of species as fragmented habitat areas re-aggregated. Analysis of fragmentation metrics (class and landscape scale) in the Weigou River Basin on the Chinese Loess Plateau showed increases in landscape heterogeneity and decreases in agricultural patch dominance [46]. Research by Fava et al [47] demonstrated that ecological processes interact with patterns of LCC and fragmentation, and thereby have implications for the success of restoration initiatives in forested areas.…”
Section: Landscape Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Maximum Likelihood Classifier (MLC) , Support Vector Machines (SVM) classifier , the landscape pattern of watershed is divided into: village and town land, farmland, water, bare land, forest land, grass and shrub land and orchard. According to the research area characteristics and other research [1][2][5][6][7][8][9][10] . Adopted in this paper, patch number and area reflect Landscape composition and the entire surface coverage condition, Shannon 's Diversity Index (abbr.…”
mentioning
confidence: 99%